WATER PRODUCTIVITY ASSESSMENTS WITH LANDSAT 8 IMAGES IN THE NILO COELHO IRRIGATION SCHEME - Teixeira, Antônio Heriberto de Castro; Leivas, Janice Freitas; Andrade, Ricardo Guimarães; Hernandez, Fernando Braz Tangerino (IRRIGA, 2015)
Water productivity assessments with Landsat 8 images in the Nilo Coelho irrigation scheme ANTÔNIO HERIBERTO DE CASTRO TEIXEIRA1; JANICE FREITAS LEIVAS1; RICARDO GUIMARÃES ANDRADE1 E FERNANDO BRAZ TANGERINO HERNANDEZ2 ¹Pesquisador doutor, grupo de Geociências, Embrapa Monitoramento por Satélite, CNPM, heriberto.teixeira@embrapa.br, janice.leivas@embrapa.br, ricardo.andrade@embrapa.br ²Professor doutor, Laboratório de Hidráulica, Universidade Estadual Paulista, UNESP, fbthtang@agr.feis.unesp.br 1 Abstract The Nilo Coelho (NC) irrigation scheme, located in the Brazilian semi-arid region, is an important irrigated agricultural area. Land use change effects on actual evapotranspiration (ET), biomass production (BIO) and water productivity (WP) were quantified with Landsat 8 images and weather data in this scheme covering different thermohydrological conditions. The SAFER algorithm was used for ET acquirements while the Monteith’s radiation model was applied to retrieve BIO. For classifying irrigated crops and natural vegetation, the SUREAL model was used with a satellite image representing the driest period of the year. The average values for ET, BIO and WP in irrigated crops, ranged, respectively, from 1.6 ± 1.9 to 4.2 ± 1.9 mm day-1; 59 ± 86 to 146 ± 91 kg ha-1 day-1;and 2.0 ± 1.5 to 3.0 ± 1.2 kg m-3. The corresponding ranges for natural vegetation (“Caatinga”) were from 1.2 ± 1.8 to 2.6 ± 1.8 mm day-1; 43 ± 78 to 76 ± 78 kg ha-1 day-1; and 1.6 ± 1.4 to 2.7 ± 1.1 kg m-3. The incremental values, which represent the effects of the replacement of natural vegetation by irrigated crops, were 40, 54 e 23%, for ET, BIO e WP, respectively. Keywords: evapotranspiration, biomass production, land use change TEIXEIRA, A.H. de C.; LEIVAS, J.F.; ANDRADE, R.G.; HERNANDEZ, F.B.T. Análises da produtividade da água com imagens Landsat 8 no perímetro de irrigação Nilo Coelho 2 resumo O perímetro de irrigação Nilo Coelho (NC), localizado na região semiárida do Brasil, é uma importante área de agricultura irrigada. Os efeitos da mudança de uso da terra na evapotranspiração atual (ET), na produção de biomassa (BIO) e na produtividade da água (PA) foram quantificados com imagens Landsat 8 e dados climáticos neste perímetro cobrindo diferentes condições termo hidrológicas. O algoritmo SAFER foi usado para a obtenção da ET enquanto que o modelo da radiação de Monteith foi aplicado para a estnimativa da BIO. Para classificação em culturas irrigadas e vegetação natural o modelo SUREAL foi usado na imagem representativa do período mais seco do ano. Os valores médios da ET, BIO e PA nas culturas irrigadas variaram respectivamente de 1,6 ± 1,9 a 4,2 ± 1,9 mm dia-1; 59 ± 86 a 146 ± 91 kg ha-1 dia-1;e 2,0 ± 1,5 a 3,0 ± 1.2 kg m-3. Os valores correspondentes para vegetação natural (“Caatinga”) foram de 1,2 ± 1,8 a 2,6 ± 1,8 mm dia-1; 43 ± 78 a 76 ± 78 kg ha-1 dia-1; e 1,6 ± 1,4 a 2,7 ± 1,1 kg m-3. Os valores incrementais, representativos dos efeitos da substituição da vegetação natural por culturas irrigadas foram de 40, 54 e 23%, para respectivamente ET, BIO e PA. Palavras-chave: Evapotranspiração, produção de biomassa, mudança de uso da terra.